Low Birth Weight as Predictor of Underweight and Stunting Among Female Students Aged 6-9 Years: an Observational Study in Surakarta - Shabrina, Amalina; Ayusari, Amelya Augusthina; Dewi, Yulia Lanti Retno; Wiboworini, Budiyanti; Sudarsono, Joko; Handayani, Sutartinah Sri; Rahayu, Dwi (Faculty of Medicine Universitas Sebelas Maret, 2024)
Introduction: Undernutrition remains a leading cause of premature mortality among children in developing countries. Previous studies discussed that the risk of undernutrition elevated with child’s age, stressing the need to address undernutrition in older children. Maternal factors also caused undernutrition through intergenerational transmission. However, data related to nutritional status of female children age >5 years in Indonesia are lacking. This study aimed to elucidate determinants associated with nutritional status among primary school girls in Surakarta.Methods: This was an observational, cross-sectional study. A total of 61 female students aged 6-9 years from Nur Hidayah Primary School Surakarta participated in this study. Data were collected through online questionnaire filled by parents who were directed to follow the procedures of anthropometric measurement at home. Z-score was calculated using WHO AnthroPlus software. Nutritional status of children was measured in weight-for-age and height-for-age. Statistical analyses were performed using Spearman’s correlation and backward linear regression. Variables with p<0.05 from the final model were considered as the determinants.Results: Among study participants, 4.9% were underweight and 9.9% were stunted. Our study found one common determinant of nutritional status by weight-for-age and height-for-age, namely birth weight (p=0.027 and p=0.011 respectively). Maternal height was, in particular, associated with nutritional status by height-for-age (p=0.001).Conclusion: Birth weight was significantly associated with nutritional status by weight-for-age and height-for-age, while maternal height was significantly correlated with only nutritional status by height-for-age. Nutrition programs for female students such as school lunch and multivitamin supplementation could be implemented to prevent the intergenerational effects of stunting and underweight.